2008
DOI: 10.1111/j.1741-3737.2008.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Expectations? Reconsidering Single Fathers’ Child‐Care Time

Abstract: We take a fresh look at an important question in the sociology of gender and family: Do single fathers ''mother''? We add to the theoretical debate by proposing that single fathers face competing interactional pressures, to simultaneously act like mothers and men. Using nationally representative data from the American Time Use Survey 2003Survey -2006, we compare the time single fathers spend on child care to other parent types, paying special attention to differences in employment profiles, household composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 28 publications
(36 reference statements)
3
56
0
6
Order By: Relevance
“…Hawkins, Amato, and King (2006) also found that single fathers were more likely than married fathers, but less likely than single or married mothers, to be involved in a wide range of children’s activities. Similarly, studies found that single mothers, although more likely than single fathers to cut back paid work demands to attend to children, spent less time in routine housework and more time in paid work than married mothers (Bianchi, Robinson, & Milkie, 2006; Hook & Chalasani, 2008). These studies suggest the importance of the intersection of marital status and gender in shaping parents’ work-family experiences.…”
Section: Marital Status Gender and Home-to-job Conflict Among Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hawkins, Amato, and King (2006) also found that single fathers were more likely than married fathers, but less likely than single or married mothers, to be involved in a wide range of children’s activities. Similarly, studies found that single mothers, although more likely than single fathers to cut back paid work demands to attend to children, spent less time in routine housework and more time in paid work than married mothers (Bianchi, Robinson, & Milkie, 2006; Hook & Chalasani, 2008). These studies suggest the importance of the intersection of marital status and gender in shaping parents’ work-family experiences.…”
Section: Marital Status Gender and Home-to-job Conflict Among Parentsmentioning
confidence: 99%
“…Prior research is unclear, however, whether the resource deficit of single parents is due to the lack of a partner or due to other factors such as a lower socioeconomic status (Kendig & Bianchi, 2008). Furthermore, research on marital status, gender, and parenting behavior has suggested the importance of considering the intersection of marital status and gender when trying to understand distributions of job and family demands among parents (Hook & Chalasani, 2008; Risman, 1998). Little is known, however, about whether single fathers differ from single mothers in home-to-job conflict.…”
mentioning
confidence: 99%
“…verhaltensleitenden Rahmungen (Goffman 1974) keine unveränder-baren, ausschließlichen und eindeutigen Gebilde darstellen, sondern selbst wiederum Verände-rungen unterliegen, die situativ reproduziert und auch transzendiert werden (können) (vgl. Raab 2014 [2008], S. 81). Einer der häufigsten Einwände, die demnach von KritikerInnen gegen Honneths Theorie der Anerkennung erhoben werden, ist daher, neben dem Vorwurf, sein Konzept setze die notwendige gesellschaftliche "Immanenz" eines kritischen Standpunktes mit "subjektiver Erfahrung" gleich (Fraser/Honneth 2003, S. 232), auch jener eines "Monismus" der Anerkennung (S. 17 ff., 284).…”
Section: Das Wissen Des Stigmasunclassified
“…An dieser ist nämlich ebenso wie die Möglichkeit des ‚befreienden' und ‚spielerischen' Umgangs mit ihr, etwa durch Formen der "Rollendistanz" oder des "impression management" (vgl. Raab 2014 [2008], S. 88 ff. ), gerade auch dort, wo es um den Zusammenhang sozialer Stigmatisierung geht, ihre regulative und normifizierende Seite gesellschaftlich wirksam und wirklich, was Goffmans "Stigma"-Schrift untrüglich vor Augen führt.…”
Section: Das Wissen Des Stigmasunclassified
See 1 more Smart Citation